2019
DOI: 10.3168/jds.2018-15013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Lactobacillus rhamnosus strain GG and tagatose as a synbiotic combination in a dextran sulfate sodium-induced colitis murine model

Abstract: Synbiotics, a combination of prebiotics and probiotics, produce synergistic effects to promote gastrointestinal health. Herein, we investigated the synbiotic interaction between the Lactobacillus rhamnosus strain GG (LGG; a probiotic strain) and tagatose (a prebiotic) in a dextran sulfate sodium (DSS)-induced colitis murine model. Initially, body weight, food intake, and clinical features were dramatically decreased after treatment with DSS, and the addition of LGG, tagatose, or both ameliorated these effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…It has been reported that d -tagatose possesses low small intestinal digestibility (15~20%) [18,19], however, it can be utilized by the intestinal microflora to increase the concentration of short-chain fatty acids (SCFAs), lower the intestinal pH, and make the intestinal environment more harmonious [15,19,20]. A previous study found that the abundance of Bacteroides , Lactobacillus , and Akkermansia was significantly associated with the tagatose treatment in the colitis murine model [21]. In view of the aforementioned cause of constipation, we hypothesized that these characteristics of d -tagatose may confer beneficial effects on relieving constipation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that d -tagatose possesses low small intestinal digestibility (15~20%) [18,19], however, it can be utilized by the intestinal microflora to increase the concentration of short-chain fatty acids (SCFAs), lower the intestinal pH, and make the intestinal environment more harmonious [15,19,20]. A previous study found that the abundance of Bacteroides , Lactobacillus , and Akkermansia was significantly associated with the tagatose treatment in the colitis murine model [21]. In view of the aforementioned cause of constipation, we hypothesized that these characteristics of d -tagatose may confer beneficial effects on relieving constipation.…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are nonpathogenic microorganisms, which when consumed in adequate amounts can confer a positive health benefit on the host (FAO/ WHO, 2006). They exert their key functions through immune-regulatory actions, thereby modifying host's immune system, by restoring gut barrier function, by lowering intestinal pH, by decreasing colonization and invasion by pathogenic organisms, and by the production of favorable metabolic products through modulation of the gut microbiota (Son et al, 2019). Recently, studies have indicated that probiotics can modify the oral microbiota, and many are under investigation to prevent or treat diseases of the oral cavity, such as dental caries and periodontal diseases (Krzyściak et al, 2017;Invernici et al, 2018;Lin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is noteworthy that the group DSS LDTM 7511 exhibited an increase and decrease pattern of the selected genera similar to the normal group ( Figure 7 b). A number of DSS colitis studies have reported a significant reduction in Bifidobacterium and induction in Enterobacteriaceae and Bacteroides [ 72 , 73 , 74 ]. Akkermansia muciniphila belonging to the phylum Verrucomicrobia is one of the generally increasing species in DSS colitis [ 75 ], and its increased abundance in DSS-treated groups was observed in this study ( Figure 5 f).…”
Section: Discussionmentioning
confidence: 99%